Cellular environment of TTR deposits in an animal model of ATTR—Cardiomyopathy - Teixeira, Cristina; Martins, Helena Sofia; Saraiva, Maria João (Frontiers in Molecular Biosciences, 2023)
This animal model of ATTR amyloidosis-cardiomyopathy and associated features observed as result of cardiac TTR deposition provide a promising and invaluable research tool for a better understanding of the implicated pathways that lead to the lethality associated to TTR cardiac amyloidosis. New therapeutic strategies can be tested and ultimately this will lead to improved treatment alternatives capable of increasing patient’s quality of life and life expectancy and, hopefully to eradicate a condition that is silently spreading worldwide.